Social Emotional Learning Integrated Arts Education in Kindergarten Indonesia and Malaysia - Muthmainah Muthmainah; Amira Najiha Binti Yahya (Aulad: Journal on Early Childhood, 2025)
This study aimed to describe art education integrated with social emotional learning in Indonesian and Malaysian kindergartens. This research approach was qualitative with a case study. The data collection methods are literature study, observation, interview, documentation, and Focus Group Discussion (FGD). Data were analyzed used the Miles, Huberman, and Saldana model. The results showed that: 1) SEL integrated art education has been conducted in both countries. In Indonesia, it includes dance, music, drama, and visual arts, while in Malaysia it includes music, drama, and visual arts; 2) SEL values that are stimulated have similarities, namely self-confidence, self-efficacy, responsibility, discipline (obeying rules), responsibility, patience, persistence, expressing and regulating emotions, respect, creative expression, cooperation, respect for differences, and empathy; 3) Challenges include lack of teacher knowledge, limited training for the development of art activities, funding, and limited art facilities. Training for developing arts activities in kindergartens needs to be provided for kindergarten teachers.